2020
DOI: 10.1186/s13756-020-00741-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of polymicrobial Staphylococcus aureus bloodstream infections

Abstract: Background: Although Staphylococcus aureus bloodstream infections (SA-BSI) are a common and important infection, polymicrobial SA-BSI are infrequently reported. The aim of this study was to investigate the clinical characteristics and risk factors of polymicrobial SA-BSI in comparison with monomicrobial SA-BSI. Methods: A single-center retrospective observational study was performed between Jan 1, 2013, and Dec 31, 2018 at a tertiary hospital. All patients with SA-BSI were enrolled, and their clinical data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
9
18
1
1
Order By: Relevance
“…Consistent with our findings, a longer length of hospital stay was also observed in patients with carbapenem-resistant KP-BSI than those with carbapenem-susceptible KP-BSI in Tian et al's study [12]. Nevertheless, differences in mortality were not significant either in our study or in other studies for polymicrobial BSI of other pathogens such as Candida, Enterococcus, Staphylococcus aureus, or A. baumannii [31,[37][38][39]. Kohler et al's meta-analysis indicated that appropriateness of empirical antimicrobial therapy was an important contributor to the observed difference in mortality between patients with carbapenem-resistant KP-BSI and patients with carbapenem-susceptible KP-BSI [40].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a longer length of hospital stay was also observed in patients with carbapenem-resistant KP-BSI than those with carbapenem-susceptible KP-BSI in Tian et al's study [12]. Nevertheless, differences in mortality were not significant either in our study or in other studies for polymicrobial BSI of other pathogens such as Candida, Enterococcus, Staphylococcus aureus, or A. baumannii [31,[37][38][39]. Kohler et al's meta-analysis indicated that appropriateness of empirical antimicrobial therapy was an important contributor to the observed difference in mortality between patients with carbapenem-resistant KP-BSI and patients with carbapenem-susceptible KP-BSI [40].…”
Section: Discussionsupporting
confidence: 91%
“…Once it happened, invasive devices such as ventilator and central venous catheterization were required. These were the major risk factors of secondary infections con rmed in many previous studies [26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 64%
“…The definition of MRD was based on the international expert proposal for interim standard [ 20 ]. Polymicrobial infection referred to ≥2 causative organisms isolated from a single blood culture [ 21 ]. Empirical antibiotic treatment was regarded as being “appropriate” if the isolated causative organisms were susceptible to ≥1 of the antimicrobial agents administered in vitro.…”
Section: Methodsmentioning
confidence: 99%